Gaining Greater Awareness of the Barriers Preventing Prospective Black Male Educators from Entering the Profession - Benson, Keith E.; Melendez-Benson, Nadine (Advances in Social Sciences Research Journal, 2025)
In effort to provide greater context for the need for more black male educators, the various approaches to recruit and retain black male educators, current issues in school discipline pertaining to urban students of color, and potential bias and discrimination that may hamper the hiring of black male educators, this summary is intended to survey each topic in a comprehensive, yet brief manner. What is clear is that there is a lack of diversity and representation in the educator workforce in America’s classrooms and students are suffering because of it - especially students of color. To the extent we care about the educational trajectory of America’s students, and our society at large, it is a must that we take whatever measures possible to provide students with what we know matters: quality curriculum that promotes cooperation and critical thinking to prepare students to be agents in their society of the future; safe and caring learning environments that dignifies students’ differences and individuality and all their complexities, and educators who are pedagogically and content proficient, as well as student-centered who honor students’ diverse cultures.